2023
DOI: 10.3758/s13428-023-02065-w
|View full text |Cite
|
Sign up to set email alerts
|

TRACK—a new algorithm and open-source tool for the analysis of pursuit-tracking sensorimotor integration processes

Abstract: In daily life, sensorimotor integration processes are fundamental for many cognitive operations. The pursuit-tracking paradigm is an ecological and valid paradigm to examine sensorimotor integration processes in a more complex environment than many established tasks that assess simple motor responses. However, the analysis of pursuit-tracking performance is complicated, and parameters quantified to examine performance are sometimes ambiguous regarding their interpretation. We introduce an open-source algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Third, previous study has shown that the response incongruent trial evokes a small beta power than the stimulus incongruent trial in the Stroop task (Zhao et al, 2015). The suppressed effect of the beta power most likely reflects the inhibition of proponent responses, associated with motion preparation (Böttcher et al, 2023;Chung et al, 2024;Wendiggensen et al, 2022;Zhao et al, 2015). Accordingly, these frequency bands can provide a comprehensive characterization of the Stroop conflict processing.…”
Section: Introductionmentioning
confidence: 99%
“…Third, previous study has shown that the response incongruent trial evokes a small beta power than the stimulus incongruent trial in the Stroop task (Zhao et al, 2015). The suppressed effect of the beta power most likely reflects the inhibition of proponent responses, associated with motion preparation (Böttcher et al, 2023;Chung et al, 2024;Wendiggensen et al, 2022;Zhao et al, 2015). Accordingly, these frequency bands can provide a comprehensive characterization of the Stroop conflict processing.…”
Section: Introductionmentioning
confidence: 99%